Community development for MSMEs on improving financial inclusion - Taufan, Bayu Adi; Maqvira (Institute for Advanced Science Social, and Sustainable Future, 2025)
Background: Positioned as the bedrock of Indonesia's economic resilience, Micro, Small, and Medium Enterprises (MSMEs) stand out as a focal point for the Indonesian government's efforts to fortify the nation's economy. The inexorable march of the Fourth Industrial Revolution requires adaptive measures by MSMEs to ensure their survival. Methods: The research examines the financial literacy levels within a community development program initiated by a financial institution, with a specific focus on the micro-business segment. Moreover, using SWOT analysis, an assessment of the community development program implemented by one of the financial institutions in Indonesia was conducted through which micro-entrepreneurs have succeeded in improving financial literacy, one of which is by having a bank account. Findings: The empowerment strategy involves imparting financial knowledge and acquainting MSME communities with digital platforms to foster their growth. Financial literacy is very important to accelerate the reach and bring financial facilities closer to the community in the form of additional capital from microcredit. Conclusion: To accelerate this process, community development initiatives and capacity-building programs for Micro and Small enterprise actors become essential, aiming to elevate their proficiency in business management, enhance production competitiveness, streamline small business enterprise management, and fulfill the evolving marketing needs of micro-business actors. Novelty/Originality of the Article: This article emphasizes the importance of financial literacy in facilitating the access to microcredit, helping micro-businesses gain financial knowledge and resources to improve their operations and sustainability.